Colombia's peace and Venezuela's turmoil: An emerging regional crisis landscape in South America - Günther Maihold (Stiftung Wissenschaft und Politik (SWP), 2018)
Despite concerted political efforts to isolate the Colombian peace process from Venezuela's internal unrest, the signs suggest coalescence and tectonic strife in the region. There are justified concerns that the increasingly interconnected constellation of precarious peace in Colombia and growing authoritarianism in Venezuela could generate new dynamics of violence. The two Andean neighbours are so closely connected by ideological confrontation, border disputes, illegal violent actors, migration flows, the narcotics trade and economic exchange that the individual problems become almost indistinguishable - both within and between the two countries. The bottom line is that the political and economic crisis in Venezuela is eroding efforts to consolidate peace efforts in Colombia. Avoiding lasting harm will require the two states to pursue integrated solutions supported by the international community.
Keywords: 320